The role of artificial intelligence and financial engineering for listed service companies in Nigeria - Ajah, Christiana Chizoba; Akintoye, Rufus Ishola; Anaekenwa, Aguguom Theophilus; Ajibade, Ayodeji Temitope (The Economics and Finance Letters, 2024)
This study examines the role of artificial intelligence (AI) in the financial engineering of listed service companies in Nigeria. The study used a survey field alongside secondary data from the financial statements of the service companies listed in the Nigerian Exchange Group. Self-structured questionnaires were administered through online platforms. The respondents were drawn from the staff of the service companies having access to AI and among the strata of practicing auditors and accountants with a clear understanding and good knowledge of AI applications and capabilities in solving financial engineering-related issues. The study utilized 487 validated responses in total. The Cronbach Alpha test was performed to confirm the validity and reliability of the instrument. Using the Statistical Program for the Social Sciences (SPSS) program, descriptive and inferential statistics were used to evaluate the obtained data. The results demonstrated that AI had a significant effect on product engineering and process engineering. Also, AI had a significant effect on financial solution engineering and, lastly, on human efficiency and productivity engineering in listed service companies in Nigeria. Managers can use the research findings to brace AI in business transactions to provide creative financial solutions, increased productivity, and increased competitiveness in the sector of digital service delivery.